POSTURE AS A THERAPEUTIC TOOL: ENHANCING BLOOD PRESSURE REGULATION THROUGH ISOMETRIC HANDGRIP AND DEEP BREATHING EXERCISES - Das, Arajit; Yadav, Dinesh Singh; Agarwal, Archana (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This study investigates the impact of different postures on the effectiveness of isometric handgrip (IHG) exercise and deep breathing (DB) techniques in managing mild hypertension among women. A total of 120 mildly hypertensive women aged 40-60 years were randomly assigned to four groups: IHG in sitting position, IHG in standing position, DB in sitting position, and DB in standing position. Blood pressure (BP) measurements were taken before and after 8 weeks of intervention. Results showed that both IHG and DB exercises led to significant reductions in systolic and diastolic BP, with the standing posture enhancing the effects for both techniques. The findings suggest that incorporating specific postures into IHG and DB exercises may optimize their antihypertensive effects in mildly hypertensive women.